Visiting Pengukur-ukuran Temple & Garba Cave in Pejeng. Remnant of Ancient Balinese Kingdom - Ida Bagus Nyoman Mertayasa (Bali Tourism Board, 2020)
Historical relics of the past are widely scattered in different areas in Indonesia, including Bali. For instance, Pejeng Village is an ancient village that was the capital city of the Old Balinese kingdom. Therefore, some archaeological sites can be found in most areas. Pengukur-ukuran Temple and Garba Cave are the heritage of the Pejeng Kingdom, in Gianyar Regency. This cave was thought to have existed since the 12th century AD. Located on the eastern bank of the Pakerisan river, the temple was one of many prominent ancient Balinese temples for the Kingdom. Some argued that the name ‘Pengukur-ukuran’ was associated with the previous King’s grand plan to measure his territory. In contrast, the others believed the term was given after General Kebo Iwa proved his invincibility in the area. The Pengukur-ukur Temple site is situated between a steep valley formed by the Pakerisan Watershed. There are temple complexes, cliff temples, and hermitage niches carved into the cliff walls on the western edge of the Pakerisan riverbank. Despite the history of the temple’s significance for the Pejeng Kingdom, Megalithic remnants found around the temple’s inner courtyard explained that the temple had been serving as a center for religious rites since prehistoric times.